(untitled) (Información, cultura y sociedad, 2005)
The article introduces periodical publication and addresses the questions raised in connection with this format, focusing on Philosophy’s journals in Argentina. Within Keresztesi’s framework of reference as regards the research/ bibliography relationship, some quantitative methods to determine indicators of representativity, visibility and vacancy of Argentinean journals in Philosophy are applied. The research examines data available in both single-discipline and multidisciplinary international and Latin-American bases. Matters arising as a result of our study are discussed and our conclusion is that the fewer the titles, the greater the visibility in international databases. Finally, we provide checked data for decision making in Philosophy information units.